2020
DOI: 10.1080/16878507.2019.1693733
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of green tea and pomegranate peel extracts on Streptococcus mutans of orthodontic treated patients

Abstract: The antibacterial effect of green tea and pomegranate peel extracts on Streptococcus mutans of orthodontically treated patients and its adherence to the tooth surface were investigated. Streptococcus mutans was isolated from saliva and plaque samples collected from orthodontic treated patients before the start of treatment and 3 months after the treatment. Gamma irradiated (5, and 10 kGy) and un-irradiated extracts of green tea leaves and pomegranate peels were prepared using polar (water, and 70% ethanol) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The content of Zn, Ti, and O 2 is from the synthesized nanoparticles. The additional elements Ca, Cu, Na, and Cl 2 are from the treated peel powder . Bayram and Ozturkcan (2021) in their research have studied that food additive Na in food packaging is advantageous for the enhancement of food shelf life and also to human health as per the World Health Organization global Na benchmark targets (2021). , Hence, 13.29% of Na identified through EDX emphasizes that the mixture remains as a real-time active agent. , Bayram and Ozturkcan (2021) have also reported that the content of chlorine in food packaging is advantageous as it incapacitates the formation of pathogens.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The content of Zn, Ti, and O 2 is from the synthesized nanoparticles. The additional elements Ca, Cu, Na, and Cl 2 are from the treated peel powder . Bayram and Ozturkcan (2021) in their research have studied that food additive Na in food packaging is advantageous for the enhancement of food shelf life and also to human health as per the World Health Organization global Na benchmark targets (2021). , Hence, 13.29% of Na identified through EDX emphasizes that the mixture remains as a real-time active agent. , Bayram and Ozturkcan (2021) have also reported that the content of chlorine in food packaging is advantageous as it incapacitates the formation of pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…The 1485–1350 cm –1 peak which appears due to the stretching vibration of CH 2 confirms the presence of carbohydrates/fats and lipids in peel powder. The 1385–1360 cm –1 peak is due to the symmetric stretching of aliphatic nitro (NO 2 ), and the 1250–950 cm –1 peak due to the vibrations of the C–H (phenyl ring) in-plane bending exhibits the presence of antioxidants, flavonoids, and tannins . Alkyl ketone (C–CO–C skeletal) vibrations at 1325–1215 cm –1 are attributed to the presence of carbohydrates in the active mixture .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors from Egypt emphasise the inhibitory effect of green tea and pomegranate peel extracts on the bacterium Streptococcus mutans and the reduction of its adherence to the tooth surface of orthodontic patients ( Abd-El-Aziz and Sallam, 2020 ). Other articles ( Eliana Harue Endo, 2012 , Noory et al, 2020 , Seeram et al, 2005 ) present published results on various aspects of of pomegranate peel polyphenols focusing on its medicinal properties.…”
Section: Antioxidant and Therapeutic Effects Of Pomegranate Peel Extractmentioning
confidence: 99%